2019
DOI: 10.1177/2040620719841591
|View full text |Cite
|
Sign up to set email alerts
|

The role of pembrolizumab in relapsed/refractory primary mediastinal large B-cell lymphoma

Abstract: Primary mediastinal large B-cell lymphoma (PMBCL) is a subtype of diffuse large B-cell lymphoma (DLBCL). PMBCL comprises approximately 10% of DLBCLs, thus making it a rare variant of DLBCL. Cure rates for PMBCL with upfront regimens like DA-REPOCH exceed 90%. However, if there is a poor response to this first-line therapy, relapsed/refractory PMBCL (rrPMBCL) has limited treatment options. The historic trend is to treat rrPMBCL with salvage regimens commonly used for DLBCL followed by high-dose therapy and auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 79 publications
0
26
0
1
Order By: Relevance
“…In the diagnosis of CHM, there are common differential diagnoses: (i) Mediastinal lymphoma: this is a malignant tumor originating from lymphoid tissue, and the common clinical manifestations are cough, hypothermia, fatigue, etc often accompanied by multiple superficial lymph node pain and enlargement, mostly in the incidence of young and middle‐aged. Chest CT features are bilateral paratracheal, posterior sternal and hilar lymph node enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…In the diagnosis of CHM, there are common differential diagnoses: (i) Mediastinal lymphoma: this is a malignant tumor originating from lymphoid tissue, and the common clinical manifestations are cough, hypothermia, fatigue, etc often accompanied by multiple superficial lymph node pain and enlargement, mostly in the incidence of young and middle‐aged. Chest CT features are bilateral paratracheal, posterior sternal and hilar lymph node enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…However, analogous to some trials in solid tumors [79] targeting the VEGF pathway in DLBCL by a combination of bevacizumab with R-CHOP (a chemotherapy regimen used for the treatment of NHL) did not significantly improve outcomes but instead increased toxicity [75]. Lymphoma cells express CD70, CD80, CD86, and PD-L1 immune checkpoints that downregulate effector T-cells including Th17 [80], and that allowed clinical approval of CIs for Hodgkin's lymphoma (HL) and primary mediastinal B-cell lymphoma [81,82]. Cancer-associated fibroblasts (CAFs) promote tumorigenic features of the microenvironment and are often studied merely within the context of bone marrow, as part of multiple myeloma and hairy cell leukemia [83].…”
Section: Immunosuppressive Microenvironment Also Matters In Lymphomamentioning
confidence: 99%
“…Given the expression of PD‐L1/2 on PMBCL cells and its known efficacy in classic Hodgkin lymphoma, pembrolizumab has been tested in adults with heavily pre‐treated r/r PMBCL. Two multicentre phase I (Keynote 013) and phase II (Keynote 170) ongoing studies have shown encouraging ORR rates of 48% and 45% respectively (Zinzani et al , 2017; Armand et al , 2019; Tomassetti et al , 2019). Based on these results, pembrolizumab was recently approved by FDA also for r/r paediatric PMBCL.…”
Section: Novel Therapiesmentioning
confidence: 99%